Project Report on Asset Tracking of a Futuristic Soldier - SAISWAROOP M, SANJAY KUMAR, SHARATH R and VENKATESH (2012)
INTERNAL GUIDE: KRISHNAMOORTHY M, MVJCE EXTERNAL GUIDE: SHRI RAJA S, SCIENTIST D CAIR DRDO
Keywords: Futuristic Soldier